Animated 'L' driving guide (panduan memandu beranimasi) / Siti Nur Aslinda Mohamad Ayob - Siti Nur Aslinda, Mohamad Ayob (2006)
The author hopes that the Animated 'L' Driving Guide courseware will manage to overcome the current accident phenomenon that always happen nowadays because of drivers' lack knowledge and most of all, carelessness. An Animated 'L' Driving Guide is one of the courseware that help students especially in guiding them about traffic rules traffic ethic and traffic sign to increase users' interest especially the students ('L' license candidates). The student will better understand the real situations of traffic signs through animation because learning driving theory from books alone is certainly not easy. The important factors of having this courseware in the education system because currently many students are having the conventional way to learn traffic rules, traffic signs and traffic ethics with lecturers supervised. Sometimes the lecturers cannot ensure whether their students able to achieve their requirement. So the teaching lesson is not convenient and less impressive. It will also enable the lecturers to teach the students as one of teaching tool in more interactive way rather than the conventional way. It also becomes one of the government initiatives to uprising the education level.